Faktor Yang Berpengaruh Terhadap Kesehatan Reproduksi Pada Pekerja Wanita Di PT. Maruki International Indonesia (Window of Public Health Journal, 2025)
There were 56,051 cases of reproductive health disorders recorded among female workers in Indonesia. The age range of workers experiencing reproductive system disorders was highest in the 25-30 year age group, with 10.8% of fatal cases for female workers during the period 2019 to 2021, so researchers were interested in studying more deeply about "Factors Influencing Reproductive Health in Female Workers at PT. Maruki International Indonesia in 2024". This study used a quantitative research method with an analytical survey method. The research design, a cross-sectional study, involved collecting data simultaneously to analyze the relationship between various factors and reproductive health. The population in this study were all female workers at PT. Maruki International Indonesia Makassar has a total of 52 people. The sampling technique used in this study was total sampling. Total sampling is a sampling method where the number of samples is equal to the number of existing populations. The results obtained are There is an influence between work period on reproductive health in workers at PT. Maruki International Indonesia Makassar in 2024, There is an influence between age and reproductive health in workers at PT. Maruki International Indonesia Makassar in 2024, There is an influence between workload and reproductive health of workers at PT. Maruki International Indonesia Makassar in 2024, There is an influence between psychological factors on PT workers' reproductive health. Maruki International Indonesia Makassar in 2024. Maruki International Indonesia Makassar in 2024. For workers, it is necessary to increase awareness about the importance of maintaining reproductive health, including a diet, exercise, and adequate rest. Furthermore, workers need to adopt stress management strategies, such as meditation or participating in relaxation activities.